Universal aspects of Efimov states and light halo nuclei - Amorim, A. E A [UNESP]; Frederico, T.; Tomio, Lauro [UNESP] (American Physical Society (APS), 1997)
The parametric region in the plane defined by the ratios of the energies of the subsystems and the three-body ground state, in which Efimov states can exist, is determined. We use a renormalizable model that guarantees the general validity of our results in the context of short-range interactions. The experimental data for one-and two-neutron separation energies, implies that among the halo nuclei candidates, only 20C has a possible Efimov state, with an estimated energy less than 14 KeV below the scattering threshold.